1992
DOI: 10.1097/00005082-199206020-00009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in family patterns six months after a myocardial infarction

Abstract: Descriptive data were gathered from 15 families on which changes in the family were reported as a result of a myocardial infarction in one family member. Persons surviving their first myocardial infarction and their families were interviewed individually and simultaneously by one of five trained interviewers in each subject's home 6 months after myocardial infarction. Data were analyzed by reduction, display, and comparison of responses. Categories of changes that emerged from the data were those in family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Few investigators have addressed the impact of cardiac arrest and ICD implantation on intimate partners and family members. What little is known about caregiving after a cardiac illness has been focused on the experiences of spouses following acute myocardial infarction or coronary artery bypass surgery (Gortner et al, 1988;Hilgenberg, Liddy, Standerfer, & Schraeder, 1992;Miller, Wikoff, Garrett, McMahon, & Smith, 1990). Attending to the needs of the family after a cardiac illness is important because patients' psychological adjustment has been linked to family function (Miller & Wikoff, 1989); patient adherence to risk factor modification has been linked to spousal anxiety and marital function (Miller et al, 1990); and caregiver strain and marital quality have been linked to increased mortality in older caregivers (Coyne et al, 2001;Schulz & Beach, 1999).…”
Section: Langloismentioning
confidence: 99%
“…Few investigators have addressed the impact of cardiac arrest and ICD implantation on intimate partners and family members. What little is known about caregiving after a cardiac illness has been focused on the experiences of spouses following acute myocardial infarction or coronary artery bypass surgery (Gortner et al, 1988;Hilgenberg, Liddy, Standerfer, & Schraeder, 1992;Miller, Wikoff, Garrett, McMahon, & Smith, 1990). Attending to the needs of the family after a cardiac illness is important because patients' psychological adjustment has been linked to family function (Miller & Wikoff, 1989); patient adherence to risk factor modification has been linked to spousal anxiety and marital function (Miller et al, 1990); and caregiver strain and marital quality have been linked to increased mortality in older caregivers (Coyne et al, 2001;Schulz & Beach, 1999).…”
Section: Langloismentioning
confidence: 99%
“…The support needs of families at times of acute illness have been highly investigated. Hilgenberg, Liddy, Standerfer, and Schraeder (1992) reported that following a spouse's myocardial infarction, positive changes in family closeness and communication may be underreported. Effects on children by the lifestyle changes needed following acute illness of parents need to be included in assessments and interventions (Hilgenberg et al, 1992;Tapp, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hilgenberg, Liddy, Standerfer, and Schraeder (1992) reported that following a spouse's myocardial infarction, positive changes in family closeness and communication may be underreported. Effects on children by the lifestyle changes needed following acute illness of parents need to be included in assessments and interventions (Hilgenberg et al, 1992;Tapp, 1995). Gilliss (1984) found that spouses experienced more stress than patients, Artinian (1989) identified that spouses are more stressed than adult children, Allen, Becker, and Swank (1991) discovered that spouses had greater difficulties with psychological adjustment 1 month following the procedure, and Gilliss, Neuhaus, and Hauck (1990) noted that interventions post-coronary artery bypass graft (CABG) surgery showed the greatest effects 8 weeks after but returned to usual patterns at 6 months.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical, psychological and social impact of critical illness on family members of the patient has been recognized in the nursing literature (Beach et al 1992, Hilgenberg et al 1992, Thompson et al 1995, Van Horn et al 2002 and the benefit of clinicians' preventative actions proposed (Hankoff et al 1974, Aguilera 1990, Cross et al 1996, Blank et al 2002, Gavaghan & Carroll 2002. However, little progress has been made to bridge the gap between such theory and specific practical applications (Somerfield & McCrae 2000).…”
Section: Introductionmentioning
confidence: 99%